2009
DOI: 10.1080/02688690802535081
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus caused by giant pituitary tumors: case series and guidelines for management

Abstract: Giant pituitary adenomas causing hydrocephalus are rare (Scarone P, Losa M, Mortini P, Giovanelli M. J Neurooncol 2006;76:51-4; Zikel OM, Atkinson JL, Hurley DL. Mayo Clinical Proc 1999;74:475-7). Guidelines for management of this rare condition are missing. Here we present a five-case series collected over 22 years. We suggest that where the two conditions coexist, the safest option is to insert an external ventricular drain prior to any definitive surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…NFGPAs causing hydrocephalus is extremely rare with only 13 cases reported in previous literatures (Table 2 ) and it lacks of guidelines for management in the past years [ 9 12 ]. What’s more, conclusions from previous case reports remain inconsistent, especially on the timing of hydrocephalus management and surgical approaches of pituitary adenomas.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…NFGPAs causing hydrocephalus is extremely rare with only 13 cases reported in previous literatures (Table 2 ) and it lacks of guidelines for management in the past years [ 9 12 ]. What’s more, conclusions from previous case reports remain inconsistent, especially on the timing of hydrocephalus management and surgical approaches of pituitary adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…What’s more, conclusions from previous case reports remain inconsistent, especially on the timing of hydrocephalus management and surgical approaches of pituitary adenomas. Four of these adenomas were reported by Joshi et al, who applied transsphenoidal surgery for patients and considered preoperative EVD as necessary to ensure the safety of subsequent operation [ 9 ]. Verhelst et al reported 1 case of NFGPA with hydrocephalus, who underwent preoperative VP shunt and transcranial surgery with unsatisfactory resection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations